1979
DOI: 10.4098/at.arch.79-18
|View full text |Cite
|
Sign up to set email alerts
|

Elements of the spatial organization of a common vole population

Abstract: 1Regina MACKIN-ROGALSKA Spatial parameters of a population of common voles Microtus arvalis (Pallas, 1779) in relation to colonies of burrows, were studied two years for two populations of these animals living in isolated fields of alfalfa each one hectare in extent. The CMR method was used. Trapping sites were set up in the centre of each colony. As the number of colonies increased their distribution changed from random to evenly spaced. In the population where density was high than this change took place alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…Our results are in agreement with findings that common voles form family groups and males may remain with females on a long-term basis and take care of the offspring (Bashenina 1962;Mackin-Rogalska 1979;Gromov 2005). The pair bond between adult male and female is regarded as weak, however (Zorenko 1979;Boyce and Boyce 1988;Gromov 2004).…”
Section: Discussionsupporting
confidence: 95%
“…Our results are in agreement with findings that common voles form family groups and males may remain with females on a long-term basis and take care of the offspring (Bashenina 1962;Mackin-Rogalska 1979;Gromov 2005). The pair bond between adult male and female is regarded as weak, however (Zorenko 1979;Boyce and Boyce 1988;Gromov 2004).…”
Section: Discussionsupporting
confidence: 95%
“…The density -dependence in the increase in the number of the colonies can result from an aggressive behaviour of adults of the same sex, or from the aggressive behaviour of the family groups (de Jonge, 1983), forcing animals to burrowing new systems. A decline in the growth rate of the number of colonies with increasing number of common voles in an isolated population, and a tendency towards a uniform distribution of colonies which may provide evidence for aggressiveness of their inhabitants, was found by Mackin-Rogalska (1979). An increase in the number of common voles with increasing number of burrow systems was significantly higher in the southern region (II a ) than in the northern region (I).…”
Section: Discussionmentioning
confidence: 86%
“…From time to time, some burrow systems are successively abandoned, temporarily or permanently for unknown reasons. Temporary abandonment and resettlement of burrow systems was described by many authors (Karaseva, 1957;Baśeni-na, 1962;Rużic, 1967;Mackin-Rogalska, 1979). Inhabited and abandoned burrow systems differed in size.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the enumeration method ("minimum number alive" or "calendar of catches"), a technique that has been widely used in central Europe to estimate population size of the common vole (Wojciechowska 1969, Adamczewska--Andrzejewska and Nabag³o 1977, Mackin-Rogalska 1979, Adamczewska-Andrzejewska et al 1981, Nabag³o 1981, consistently gave lower estimations of population size when compared to the JS model. The negative bias increased with density, decreased with increasing capture probability and was more pronounced in males at high density.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the Jolly-Seber model (JS; Jolly 1965, Seber 1965) and its special model variants have turned out to be particularly useful in long-term microtine studies, as they allow estimation of population size at each sampling time as well as survival rates and birth numbers between sampling times (Pollock et al 1990). However, the capture-recapture data on common voles have been almost exclusively evaluated by means of the enumeration estimators (eg Adamczewska-Andrzejewska and Nabag³o 1977, Mackin-Rogalska 1979 yielding population size estimates, which also are known as minimum number alive (MNA; Krebs 1966) or calendar of catches (Petrusewicz and Andrzejewski 1962). Unlike the JS method, which handles recaptures within the clearly defined framework of probabilistic models based strictly on a statistical theory, the enumeration method uses recaptures only as a means of establishing that a marked individual was alive in some previous sampling period when it was caught (Pollock et al 1990).…”
Section: Introductionmentioning
confidence: 99%